The role of green coffee extract on weight loss glucose and lipid metabolism - Fasihi, Mehdi; Barzegar, Ali; Alizadeh Sani, Mahmood (Progress in Nutrition, 2020)
The purpose of this paper was to perform a review about the role of green coffee extract on weight loss, glucose and lipid metabolism. It has been shown that overweight and obesity are important problems for health and the financial and psychological aspects have been imposed many damages to governments and health care providers. The management of overweight and obesity is related to lifestyle, physical activity, and diet. In the past decade, the studies have been published about the effects of green coffee extract on hypoglycemic, weight losing and hypotensive have been increasing. there are limited number of human studies in this area. However, the majority of interventional and epidemiological studies have been shown the beneficial effects of green coffee extract on weight and blood glucose management and metabolism of lipids. Green coffee extract reduces the fat reserves in adipocytes and regulate blood glucose by several mechanisms. Accordingly, green coffee extract supplementation may be effective in weight management, glucose and lipid metabolism.